PELESTARIAN MAKAM SYEKH ABDURRAHMAN SIDDIQ MELALUI PENGENALAN HUKUM TATANEGARA DALAM FESTIVAL KAMPUNG - Ali Azhar; KMS Novyar Satriawan Fikri, Mulono Apriyanto (JOURNAL OF COMMUNITY DEDICATION, 2022)
Teluk Dalam Village has a special cultural potential due to its history and culture, which reveal a religious leader in Riau's past. However, the region has not been able to adequately manage the tourism potential or earn cash from it. The team designed cultural preservation initiatives through community support programs in order to discover new tourist attractions, preserve and document historic structures and artifacts, and package tourist attractions for performances at village festivals. The employment of debriefing, coaching, and training is employed to aid. After that, attractions are advertised via social media. The results of the mentorship programs indicate an increase in cultural preservation knowledge, expertise, and concern, all of which have an impact on the community's potential new sources of income. Teluk Dalam Village's village festival festivities successfully preserve historical legacies and different cultural customs.